Analisis Konsep Penerapan Murabahah Berdasarkan PSAK 102 pada Perbankan Syariah di Indonesia - Dwi Rahma Fita Hamida; Siti Afidatul Khotijah (Universitas Kristen Maranatha, 2022)
This research was conducted by Islamic banking in Indonesia. This article analyzes the concepts of murabahah financing, this is done because there are still deviations in the application of murabahah financing, namely the difference between the rules of murabahah financing and existing practices in the field. In this article, we compare the existing regulations with the practical situation in the field by involving some information (practitioners and customers concerned) as well as some other supporting literature. This study aimed to analyze whether murabahah financing by Indonesian Islamic banks complies with PSAK 102 in relation to murabahah. This study reveals how Islamic banks in Indonesia handle Murabahah credit. The nature of this research is a descriptive qualitative approach. This study has two data sources, namely primary data sources and secondary data sources. To obtain valid data, researchers used data collection methods, namely documentation. After the data was collected, the researcher used an inductive method to analyze with qualitative data analysis techniques. Based on the results of this study, it can be shown that in practice the public only knows about the existence of Islamic banks but does not understand Islamic banks in detail. Only some people know about Islamic banking and some people know nothing about Islamic banking. Most people do not know the products and services offered by Islamic banks. However, the application of murabahah in Islamic banking practice is divided into three categories: The first type is consistent with muamalah fiqh. The second type is similar to the first type, there is a direct transfer of ownership from the supplier to the customer, while the payment is made by the bank directly to the first seller/supplier the third type is a bank with a Murabahah agreement with the customer and represents (wakalah contract) to the customer to purchase goods. The lack of public awareness is due to the lack of available information about Islamicbanks, causing the public to not know what Islamic banks are and what products are owned by Islamic banks, namely PSAK 102. Keywords: Islamic Banking, Murabahah, PSAK 102